A new category stent with novel polyphosphazene surface modification. (27th March 2018) - Mori, Hiroyoshi; Jinnouchi, Hiroyuki; Diljon, Chahal; Torii, Sho; Sakamoto, Atsushi; Kolodgie, Frank D; Virmani, Renu; Finn, Aloke V
The COBRA-PzF™ (CeloNova BioSciences, Inc., TX, USA) is a new type of coronary stent composed of a cobalt chromium metallic backbone surrounded by a nanothin layer of Polyzene-F (PzF) without any added drug. Evidence from basic studies supports antithrombotic and anti-inflammatory properties for the PzF surface coating. Preclinical studies support the thromboresistance of PzF-coated surfaces and clinical studies have shown good outcomes for patients receiving this device with very low rates of stent thrombosis. COBRA-PzF may be especially useful in patients at high risk for bleeding. Ongoing clinical trials will determine whether shortening the duration of dual antiplatelet therapy to less than 1 month is feasible and these data may represent a new paradigm with regards to patients at high risk for bleeding.